One-step chemical vapor deposition synthesis and supercapacitor performance of nitrogen-doped porous carbon–carbon nanotube hybrids - Lobiak, Egor V.; Bulusheva, Lyubov G.; Fedorovskaya, Ekaterina O.; Shubin, Yury V.; Plyusnin, Pavel E.; Lonchambon, Pierre; Senkovskiy, Boris V.; Ismagilov, Zinfer R.; Flahaut, Emmanuel; Okotrub, Alexander V. (Beilstein Journal of Nanotechnology, 2017)
Novel nitrogen-doped carbon hybrid materials consisting of multiwalled nanotubes and porous graphitic layers have been produced by chemical vapor deposition over magnesium-oxide-supported metal catalysts. CNx nanotubes were grown on Co/Mo, Ni/Mo, or Fe/Mo alloy nanoparticles, and MgO grains served as a template for the porous carbon. The simultaneous formation of morphologically different carbon structures was due to the slow activation of catalysts for the nanotube growth in a carbon-containing gas environment. An analysis of the obtained products by means of transmission electron microscopy, thermogravimetry and X-ray photoelectron spectroscopy methods revealed that the catalyst's composition influences the nanotube/porous carbon ratio and concentration of incorporated nitrogen. The hybrid materials were tested as electrodes in a 1M H2SO4 electrolyte and the best performance was found for a nitrogen-enriched material produced using the Fe/Mo catalyst. From the electrochemical impedance spectroscopy data, it was concluded that the nitrogen doping reduces the resistance at the carbon surface/electrolyte interface and the nanotubes permeating the porous carbon provide fast charge transport in the cell.
Keywords: bimetallic catalyst; electrochemical impedance spectroscopy; N-doped carbon; porous carbon–carbon nanotube hybrid; supercapacitor